Forced and natural carbonation of lime-based mortars with and without additives: Mineralogical and textural changes - Cultrone, G.; Sebastián, E.; Huertas, M. Ortega (Cement and concrete research, 2005)
We have studied the carbonation process in different types of mortars, with and without pozzolana or air-entraining additives, subject to a CO 2-rich atmosphere and compared the results with those of similar naturally carbonated mortars. We used X-ray diffraction technique to demonstrate that high CO 2 concentrations favour a faster, more complete carbonation process with 8 days being sufficient to convert portlandite into 90 wt.% calcite. Full carbonation, however, is not reached during the life-span of the tests, not even in forced carbonation experiments. This could be due to at least one of the following phenomena: a premature drying of samples during carbonation reaction, the temperature at which the carbonation process was carried out or the reduction of pore volume occupied by newly formed calcite crystals. This last option seems to be the least probable. We observed a more prolific development of calcite crystals in the pores and fissures through which the carbonic anhydride flows. Under natural conditions, carbonation is much slower and similar levels are not reached for 6 months. These differences suggest that the carbonation process is influenced by the amount of CO 2 used. Both the mineralogy and texture of mortars vary depending on the type of additive used but the speed of the portlandite–calcite transformation does not change significantly. Pozzolana produces hydraulic mortars although the quantity of calcium aluminosilicate crystals is low. The air-entraining agent significantly alters the texture of the mortars creating rounded pores and eliminating or reducing the drying cracks.